ASAS KONSENSUALISME DALAM INFORMED CONSENT ANTARA DOKTER DENGAN PASIEN - Lintang Yudhantaka; Mas Anienda Tien Fitriyah; Rosalia Dika Agustanti (Hang Tuah Law Journal, 2021)
The term informed consent or consent for particular medical treatment was familiar in medical world. It brought security for both doctors who did their profession and patients who got information about the illness they were suffering from along with any medical treatment they would have. In fact, there were still many problems issued due to less-well implementation of informed consent. Therefore, this study aimed to analyze the characteristics of informed consent as the legal basis between doctor and patient and verify the establishment of agreement (i.e., consensus) in informed consent. It was a juridical-normative research with conceptual and statute approaches. The result of this study found that informed consent had distinctive characteristics compared with any other common agreements, in particular to its subject, object, and cause. Towards the establishment of consensus, it referred to the doctor’s offering to do any medical treatment and patient’s acceptance to have that treatment.